Insights on TPACK Implementation by Preservice English Teachers: Challenges and Solutions - Endang Darsih; Vina Agustiana; Agie Hanggara; Roger Palmer (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: A crucial issue in teacher education today is ensuring that PTs are well prepared to integrate technology into their future classrooms. This study examines the implementation of Technological Pedagogical Content Knowledge (TPACK) among preservice English teachers in planning and implementing learning, as well as the barriers they face and their solutions.Methodology: This study used a case study research design to explore in depth how PTs apply the TPACK framework in real classroom situations. The participants in this study consisted of five PTs from teacher education programs at four universities in Indonesia.Findings: PTs generally show good alignment between technology use, pedagogical strategies, and content in their lesson plans, but are often not optimally integrated during implementation. The main barriers identified include limited access to and technology resources, differences in technology skill levels between students and teachers, students' difficulties in adapting to technology-based learning, and time management issues. The solutions are to provide device assistance to students in need, provide basic technology training and plan carefully and provide realistic time for students to adapt to technology and complete assignmentsConclusion: To enhance technology integration in education, universities must prioritize providing device assistance and basic tech training for PTs. By addressing these barriers, educators can better support effective technology use in the classroom, ultimately improving student learning outcomes.Originality: How pre-service teachers, who are the next generation of educators, develop and implement TPACK during their preparation and learning phases. In particular, there is very little research that specifically explores the implementation of TPACK in the classroom by PTs, as well as a lack of exploration of the challenges faced by them and the strategies used in the TPACK integration process.